Energy Harvesting Untethered Soft Electronic Devices. Issue 17 (30th April 2021) - Kim, Kyun Kyu; Choi, Joonhwa; Ko, Seung Hwan
Abstract: Advances in wearable and stretchable electronic technologies have yielded a wide range of electronic devices that can be conformably worn by, or implanted in humans to measure physiological signals. Moreover, various cutting‐edge technologies for battery‐free electronic devices have led to advances in healthcare devices that can continuously measure long‐term biosignals for advanced human–machine interface and clinical diagnostics. This report presents the recent progress in battery‐less, wearable devices using a wide range of energy harvesting sources, such as electromagnetic energy, mechanical energy, and biofuels. Additionally, this report also discusses the principles and working mechanisms of near/far‐field communications, triboelectric, thermoelectric, and biofuel technologies. Abstract : Recent development of untethered devices consists of a range of cutting‐edge technologies such as electromagnetic, triboelectric, and thermoelectric energy harvesting devices. Recent advances in the bio‐fuel‐based electronics show numerous solutions to the remaining practical issues of continuous measurement without an external power source. Key advancements in untethered devices in various power sources are introduced with their principles and working mechanisms.